2008
DOI: 10.1590/s0103-64402008000400002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative radiographic evaluation of periapical bone resorption in dog's teeth contaminated with bacterial endotoxin (LPS) associated or not with calcium hydroxide

Abstract: The aim of this study was to quantify radiographically the periapical bone resorption in dogs' teeth contaminated with bacterial endotoxin (LPS), associated or not with calcium hydroxide. After pulp tissue removal, 60 premolars were randomly assigned to 4 groups and were either filled with LPS (group 1), filled with LPS plus calcium hydroxide (group 2) or filled with saline (group 3) for a period of 30 days. In group 4, periapical lesion formation was induced with no canal treatment. Standardized radiographs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
0
8
0
11
Order By: Relevance
“…2011). In an in vivo study, da Silva et al. (2008) concluded that calcium hydroxide was effective in inactivating LPS as demonstrated by the absence of periodontitis in roots simultaneously filled with the two agents.…”
Section: Discussionmentioning
confidence: 99%
“…2011). In an in vivo study, da Silva et al. (2008) concluded that calcium hydroxide was effective in inactivating LPS as demonstrated by the absence of periodontitis in roots simultaneously filled with the two agents.…”
Section: Discussionmentioning
confidence: 99%
“…Among the beneficial properties of calcium hydroxide are its biocompatibility (10,11), antibacterial activity (12), induction of mineralized tissue formation (13)(14)(15), activation of alkaline phosphatase and collagen synthesis (16) and ability to produce hydrolysis of bacterial endotoxin (17).…”
Section: Introductionmentioning
confidence: 99%
“…This stimulates the synthesis and release of cytokines that activate osteoclasts, such as IL-1 and TNF, as previously described, and also stimulates the release of prostaglandin E2, which also has an influence on these cells 8,31 .…”
Section: Etiology Of Periapical Lesions and The Role Of Endotoxin In mentioning
confidence: 53%